A new species of Goneplax Leach, 1814 (Crustacea, Decapoda, Brachyura, Goneplacidae) from the south Atlantic and the western limits of the Indo-West Pacific region, long confused with G. rhomboides (Linnaeus, 1758) - Guinot, Danièle; Castro, Peter (Zootaxa, 2007)
A new species of Goneplax Leach, 1814, G. clevai n. sp., is described from the South Atlantic and the western limits of the Indo-West Pacific region. The new species was for a long time confused with G. rhomboides (Linnaeus, 1758), senior synonym of Cancer angulata Pennant, 1777, Ocypoda bispinosa Lamarck, 1801, Ocipode [sic] longimana Latreille, 1803, Goneplax rhomboїdalis Risso, 1827, and Gelasimus bellii Couch, 1838. Goneplax rhomboides is found in the northeastern Atlantic and the Mediterranean Sea. Museum collections contain mixed material belonging to the two species. Carcinoplax barnardi Capart, 1951, which is close to Goneplax, is also present in the South Atlantic, its distribution overlapping that of the new species. The sympatry of G. rhomboides and G. clevai n. sp. is uncertain owing to the absence of information on the southern limit of G. rhomboides.